Low Dose-Rate Interstitial Brachytherapy in Soft Tissue Sarcomas. (1999) - Rosenblatt, Edward; Meushar, Netanel; Eidelman, Mark; Kuten, Abraham
Abstract : Purpose. To assess the effectiveness of Ir-192 interstitial brachytherapy as an adjunct to wide local excision as a functionsaving strategy for soft tissue sarcomas. Subjects and methods. From September 1993 to April 1998, 20 consecutive patients diagnosed with soft tissue sarcomas were treated with a combination of wide local excision and interstitial brachytherapy. In 16 patients brachytherapy was done as an intraoperative procedure, while in four, the implant was performed post-operatively under local anesthesia. Eleven of the 20 patients also received external beam radiotherapy following the implant. Results. After a mean follow-up of 27 months (4–54) the local control rate for all 20 patients was 85% (17/20). In the 16 patients who had an intra-operative implant, local control was 94% (15/16). In the four patients who underwent a post-operative implant, local control was 50% (2/4). Actuarial 5-year survival was 90%. There were three cases (15%) of severe local complications. Conclusions. Wide local excision followed by low dose rate intersitital brachytherapy have yielded a 85% local control rate in 20 patients with soft tissue sarcomas. Local control rates were higher when the implants were done as an intra-operative procedure than as a post-operative one.